2011
DOI: 10.1177/0954406211423324
|View full text |Cite
|
Sign up to set email alerts
|

Control of shroud leakage flows to reduce mixing losses in a shrouded axial turbine

Abstract: The losses caused by the leakage flows through the rotor tip clearance, and the mixing losses by the re-entering leakage into the main flow are considerable parts of the total losses in turbines. The main reason for the mixing losses is the different velocity components of main and leakage flows. This leads to shear stresses which cause increased turbulence and losses. This article presents a numerical investigation on three different configurations to control the leakage flows: (a) turning vanes are fixed ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Besides, considering there is a very complex flow occurs in the tip clearance, a validation was also performed using the numerical data of Lin et al 24 Figure 17 shows the comparison of the current predictions with the numerical data for S dis distributions taken at a staggered labyrinth seal. S dis is the entropy generation rate, which is expressed by equations (14) and (15). It can be seen that, the distribution of viscous loss agrees well, especially in throttle regions and stagnation points.…”
Section: Comparison Of Mixing Loss Under Different Tip Clearancesmentioning
confidence: 64%
See 2 more Smart Citations
“…Besides, considering there is a very complex flow occurs in the tip clearance, a validation was also performed using the numerical data of Lin et al 24 Figure 17 shows the comparison of the current predictions with the numerical data for S dis distributions taken at a staggered labyrinth seal. S dis is the entropy generation rate, which is expressed by equations (14) and (15). It can be seen that, the distribution of viscous loss agrees well, especially in throttle regions and stagnation points.…”
Section: Comparison Of Mixing Loss Under Different Tip Clearancesmentioning
confidence: 64%
“…The above researches only corrected the leakage loss, without considering that the leakage flow not only leads to the mixing loss, but also changes the downstream stator flow field and causes additional secondary flow loss. Gao et al 15 studied the effect of tip clearance on the aerodynamic characteristics of a supersonic turbine stage. Similarly, experimental and numerical investigations were proposed by Peters et al 16 to study the tip leakage flow, the flow angle at the rotor, and downstream stator blade exit with the six different tip clearances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not investigate the robustness of the design to increases in clearance. Numerical calculations by Gao et al [12] suggested that the turning vane design is not robust to increases in clearance and would become less effective over the operational life of the turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.12:A two-dimensional diagram to illustrate how the pressure side boundary layer radial vorticity filaments are turned towards the positive streamwise direction at the separation point 12. …”
mentioning
confidence: 99%